The Effectiveness of The Supervision By The Regional Supervisory Council Over Notaries Based On Article 67 Paragraph (5) of The Notary Office Act - Intan Nirmala Ramadhani; Hanif Nur Widhiyanti; Diah Aju Wisnuwardhani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This study examines the effectiveness of supervision by the Malang Raya Regional Supervisory Council (MPD) on the behavior and implementation of notary positions based on Article 67 paragraph (5) of the Notary Position Law. The background of the study is that there are still notaries who do not carry out their duties according to the provisions, so that effective supervision is important. The study uses an empirical method (sociolegal) with a legal and conceptual sociology approach, through interviews, observations, and literature studies. The results of the study indicate that supervision by the MPD is normatively in accordance with the rules, but in practice it is not optimal. Limited intensity, the absence of supervisory mechanisms at times, and a focus more on administrative aspects than professional ethics make the effectiveness of supervision low. The main obstacles include the lack of MPD members, the absence of firm sanctions, and low awareness of notaries. As a result, supervision does not fully reflect the principles of accountability, transparency, and the function of professional development. The study concludes that institutional strengthening, consistent enforcement of sanctions, and ethical development are needed to improve notary professionalism.